A robust octahedral NiCoOxSy core-shell structure decorated with NiWO4 nanoparticles for enhanced electrocatalytic hydrogen evolution reaction. (20th January 2023) - Yang, Yaoxia; Zhang, Lan; Guo, Fengyao; Wang, Dangxia; Guo, Xingwei; Zhou, Xiaozhong; Sun, Dongfei; Yang, Zhiwang; Lei, Ziqiang
Highlights: A hierarchical core-shell NiWO4 @NiCoOx Sy /NCF heterostructure has been fabricated on Ni-Co foam by in situ engineering approach and typical hydrothermal-annealing treatments. The NiCoOx Sy octahedrons offer intrinsic catalytic activity as well as the NiWO4 nanoparticles avoid collapse of internal structure. The strong linkage of roughened octahedrons to un-smooth nanoparticles provides large specific surface area, accelerates electron transport, and facilitates gas releasing. The NiWO4 @NiCoOx Sy /NCF and NiCoOx Sy /NCF present low overpotential and superior stability toward HER, respectively. The as-prepared NiWO4 @NiCoOx Sy /NCF electrode is far surpassing most of the reported bimetallic oxides or sulfides electrocatalysts. Abstract: Electrocatalytic hydrogen evolution reaction by water splitting is deemed to a clean and efficient approach for greener energy. The intensive pursuit of cost-effective and stable electrocatalysts for HER is quite imperative and challenging. Herein, a typical core-shell NiWO4 @NiCoOx Sy /NCF nano-architecture consisted of NiCoOx Sy /NCF octahedrons and NiWO4 nanoparticles on nickel-cobalt foam is synthesized, and the NiWO4 @NiCoOx Sy /NCF requires quite small overpotential of 85 mV to afford current density of 10 mA cm −2 for HER in 1 M KOH, respectively, while NiCoOx Sy /NCF shows the overpotential of 132 mV at the current density of 10 mA cm −2 in 0.5 M H2 SO4 . Moreover, they still present good durability with continuous operation of 72 h in alkaline and acidic electrolytes, outperforming most of the non-noble bimetallic oxides or sulfides electrocatalysts. The prominent performance benefits from NiWO4 @NiCoOx Sy /NCF takes advantages of component respective strengths such as interfacial cooperative effect, strong electrical connection and fast electron transfer, the highly exposed surface area, in situ surface reconstruction. The work provides a new prospect toward the controlled design and rational fabrication of multicomponent hierarchical core-shell structure electrocatalyst in high-performance flexible electrochemical hydrogen production. Graphical abstract: Image, graphical abstract